Aplicação de cavacos de titânio para produção de revestimentos resistentes ao desgaste - Fagundes Júnior, José Gedael [UNESP]; Manera, Rodolfo Da Silva; Tokimatsu, Ruís Camargo [UNESP]; Ventrella, Vicente Afonso [UNESP]; Gallego, Juno [UNESP] (Associação Brasileira de Soldagem, 2014)
Equipments of the sugar-cane plants and mineral extraction are submitted to severe abrasive wear conditions. Welded hardfacing are usually applied to repair that kind of damage where commercial chromium/carbon-rich welding consumables have usually been employed. In the present work was investigated the microstructure of experimental hardfacings made by addition of residues (chips) collected from machining of ASTM F67 (unalloyed Ti, grade 4) alloy. Mixtures with different carbide-formers (Cr/Nb ferro-alloys) were also tested. Two layers of pure chips (Ti), chips plus Fe-Cr (Ti-Cr), and chips plus Fe-Nb (Ti-Nb) were applied on low-carbon steel specimens by GTAW/TIG process. The microstructure of hardfacing layers was observed by optical and scanning electron microscopy (SEM) equipped with EDS microanalysis. The microstructural characterization has determined that carbide distributions change significantly with the chemical nature of the hardfacing. SEM observations coupled with EDS microanalysis have confirmed the formation of complex carbides within metal weld, whose stoichiometry was determined by X-rays diffraction (XRD) analysis. Mixed carbides MC-type and some cementite have been found. As a result it was suggested that using of ASTM F67 chips as carbide formers for composition of welding consumables can contribute to improve wear resistance of hardfacings, if compared with traditional chromium-based hardfacings.

Equipamentos usados nas usinas sucroalcooleiras e de extração mineral são submetidos a condições severas de desgaste abrasivo. Revestimentos duros são usualmente aplicados para reparar este tipo de dano, sendo bastante empregados consumíveis de soldagem contendo altos teores de cromo e carbono. No presente trabalho visa investigar a microestrutura de revestimentos duros formados com a fusão de cavacos de titânio puro ASTM F67 grau 4, material usado na fabricação de implantes odontológicos. Misturas com diferentes formadores de carbonetos (Fe-Cr e Fe-Nb como aditivos) também foram testadas. Revestimentos feitos com duas camadas de cavacos puros (Ti), cavacos com Fe-Cr (Ti-Cr) e cavacos com Fe-Nb (Ti-Nb) foram depositadas sobre peças de aço-carbono por soldagem TIG/GTAW. A microestrutura das camadas foi observada com microscópio óptico e por microscópio eletrônico de varredura equipado com microanálise. A caracterização microestrutural revelou que a distribuição de carbonetos varia significativamente com a natureza química dos aditivos usados. A microanálise mostrou que houve a formação de carbonetos com composição química complexa no seio do metal de solda, cuja estequiometria foi determinada com análise por difração de raios-X. Carbonetos mistos do tipo MC e cementita foram identificados. Os resultados apresentados indicam que a aplicação de cavacos de titânio ASTM F67, como insumo para formação de carbonetos, pode contribuir para melhorar a resistência ao desgaste em comparação aos tradicionais revestimentos duros com carbonetos de cromo.
Application of titanium machining chips in welding consumables for wear resistant hardfacing
Keywords: soldagem GTAW; revestimento duro; carbonetos; reciclagem de titânio; microestrutura; resistência ao desgaste; GTAW/TIG welding; hardfacing; carbides; titanium chips recycling; microstructure; wear resistance